Prevalence and Genetic Characterization of Chlamydia spp. in Captive Reptiles in Zoos, Chiang Mai - Boonsri, Kittikorn; Boontong, Pinich; Dechkajorn, Sakorn; Kong-ngoen, Fahdaow; Pringproa, Kidsadagon (Journal of Mahanakorn Veterinary Medicine, 2022)
This study investigated the prevalence of chlamydia among captive reptiles in zoos, Chiang Mai, Thailand. The method was conducted by polymerase chain reaction (PCR) of the 16S rRNA gene and further characterized these bacteria by performing phylogenetic analysis of the sequences of the variable domain 2 (VD2) region of the ompA gene, with encodes the Chlamydia major outer membrane protein. Cloacal swabs were collected from 115 reptile animals in two zoos and examined for their genus and species specification. The prevalence of Chlamydia spp., C. psittaci and C. pneumoniae were found to be 9.57%, 9.57% and 0%, respectively. Phylogenetic analysis from 11 samples showed that three samples were similar to C. psittaci and eight samples were C. pecorum. This study demonstrated for the fixed time that diverse Chlamydia species could be found in asymptomatic reptiles in zoos of Chiang Mai province. Therefore, disease monitoring is necessary to prevent and control clamydiosis in zoo animals.